2023
DOI: 10.1021/acs.jmedchem.3c00613
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activities of DNA-Alkylating Pyrrole–Imidazole Polyamide Analogs Targeting RUNX Transcription Factors against p53-Mutated Pancreatic Cancer PANC-1 Cells

Yuki Hirose,
Shinsuke Sato,
Kaori Hashiya
et al.

Abstract: The runt-related transcription factor (RUNX) family is known to play important roles in the progression of cancer. Conjugate 1, which covalently binds to the RUNX-binding sequences, was reported to inhibit the binding of RUNX proteins to their target sites and suppress cancer growth. Here, we evaluated the anticancer effects of 1 and its analogs 2–4 against p53-mutated PANC-1 pancreatic cancer cells. We found that they possessed different DNA-alkylating properties in vitro. And conjugates 1–3 were shown to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…By treating cells with 0.3 or 3 μM of the compound, cell populations shifted to the lower right (early apoptotic cells) and upper right (late apoptotic cells) parts of the plot (Figure ). This indicated that Chb-M′ killed p53 -mutated NSCLC cells by inducing apoptosis, as it did in other p53 -WT and p53 mutant cancer cells. ,, …”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…By treating cells with 0.3 or 3 μM of the compound, cell populations shifted to the lower right (early apoptotic cells) and upper right (late apoptotic cells) parts of the plot (Figure ). This indicated that Chb-M′ killed p53 -mutated NSCLC cells by inducing apoptosis, as it did in other p53 -WT and p53 mutant cancer cells. ,, …”
Section: Resultsmentioning
confidence: 72%
“…In spite of the anticancer effect of Chb-M′ against NCI-H2228-Luc cells, when we conducted the same experiment with BJ cells (human normal fibroblast cell line) to evaluate the toxicity of the compounds, all compounds did not show any toxicity against this cell line after treatment for 3 days (Figure S5). Although this result suggested the low toxicity of Chb-M′ against normal cells, it is also the fact that this compound decreased the viability of human normal pancreas duct cells (viability was ∼80%) in our previous research . It is still less toxic than that against NCI-H2228-Luc cancer cells, but evaluation of the toxicity of this compound should be performed in more detail in the future.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Apoptosis produces cellular alterations, such as phosphatidylserine (PS) translocation from inside to outside the plasma membrane. Annexin-V, a sensitive probe that binds to PS, may detect it outside the plasma membrane. , We performed cytometric analysis using the BD FACSCalibur (BD Biosciences, San Jose, CA) to distinguish between the apoptotic and necrotic modes of pancreatic PANC1 cells’ death as a result of the most active compound, 5e . Figure S59 shows the outcomes of compound 5e ’s 24 h treatment of PANC1 cells.…”
Section: Resultsmentioning
confidence: 99%